2022
DOI: 10.1111/jfd.13719
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics, optimal dosages and withdrawal time of florfenicol in Asian seabass (Lates calcarifer) after oral administration via medicated feed

Abstract: Asian seabass (barramundi, giant seaperch, Lates calcarifer) is a popular food fish in Asia and Australia. Native to coastal areas of the Indo-West Pacific, it can now be found from the Persian Gulf to China and northern Australia, either in coastal marine, estuarine, or freshwater habitats (Pethiyagoda & Gill, 2012;Rimmer, 2006). The Asian seabass culture technique was first developed in Thailand during the 1970s (Cheong, 1989;Rimmer, 2006). Since then, Asian seabass farming has been expanded and developed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Analytical methods for determination of the FF and/or its metabolite florfenicol amine (FFA) in blood samples, edible tissues or drug formulations are primarily described in the literature. For example, the following methods were used: voltammetric method [ 13 ], enzyme-linked immunosorbent assay (ELISA) method [ 14 ], ultraviolet-visible (UV-Vis) spectrophotometric method [ 15 ], near-infrared spectroscopy [ 16 ], capillary electrophoresis [ 17 ], and chromatographic methods such as thin-layer chromatography (TLC) [ 18 ], gas chromatography (GC) [ 19 ], (ultra)high-performance liquid chromatography ((U)HPLC) with ultraviolet (UV), diode array detector (DAD) or fluorescence (FL) detector [ 20 , 21 , 22 , 23 , 24 , 25 ], and liquid chromatography-tandem mass spectrometry (LC-MS/MS) [ 26 , 27 , 28 , 29 ]. Only several reported papers included and described the analytical methods for determining the FF in urine samples of animal origin [ 1 , 11 , 12 , 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analytical methods for determination of the FF and/or its metabolite florfenicol amine (FFA) in blood samples, edible tissues or drug formulations are primarily described in the literature. For example, the following methods were used: voltammetric method [ 13 ], enzyme-linked immunosorbent assay (ELISA) method [ 14 ], ultraviolet-visible (UV-Vis) spectrophotometric method [ 15 ], near-infrared spectroscopy [ 16 ], capillary electrophoresis [ 17 ], and chromatographic methods such as thin-layer chromatography (TLC) [ 18 ], gas chromatography (GC) [ 19 ], (ultra)high-performance liquid chromatography ((U)HPLC) with ultraviolet (UV), diode array detector (DAD) or fluorescence (FL) detector [ 20 , 21 , 22 , 23 , 24 , 25 ], and liquid chromatography-tandem mass spectrometry (LC-MS/MS) [ 26 , 27 , 28 , 29 ]. Only several reported papers included and described the analytical methods for determining the FF in urine samples of animal origin [ 1 , 11 , 12 , 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…It can also be an alternative sample to edible tissues, for example, for mon antibiotic administration [11] or detecting an appropriate time of animal slaughter (a) (b) Analytical methods for determination of the FF and/or its metabolite flor amine (FFA) in blood samples, edible tissues or drug formulations are primarily des in the literature. For example, the following methods were used: voltammetric m [13], enzyme-linked immunosorbent assay (ELISA) method [14], ultraviolet-visibl Vis) spectrophotometric method [15], near-infrared spectroscopy [16], capillary e phoresis [17], and chromatographic methods such as thin-layer chromatography [18], gas chromatography (GC) [19], (ultra)high-performance liquid chromatog ((U)HPLC) with ultraviolet (UV), diode array detector (DAD) or fluorescence (FL) d [20][21][22][23][24][25], and liquid chromatography-tandem mass spectrometry (LC-MS/MS) [ Only several reported papers included and described the analytical methods for mining the FF in urine samples of animal origin [1,11,12,[30][31][32][33]. However, employ verse and often complex analytical techniques in FF analyses indicated that their on the environment should also be considered.…”
Section: Introductionmentioning
confidence: 99%